THE COLLABORATIVE GOVERNANCE IN THE RUMAH PENTING PROGRAM: A STUDY ON STRENGTHENING ADOLESCENT PARTICIPATION IN STUNTING MITIGATION IN JEMBRANA REGENCY - I Kadek Marssel Bagia Sedana; Dedy Pribadi Uang (Journal of Social Politics and Governance (JSPG), 2026)
This study aims to analyze the role of adolescent participation through the Rumah Penting initiative in addressing stunting in Jembrana Regency, Bali Province. This study employs the collaborative governance theory proposed by Chris Ansell and Alison Gash (2008), which emphasizes four key dimensions: initial conditions, facilitative leadership, institutional design, and collaborative processes in achieving collective outcomes. A qualitative case study approach was applied, with data collected through interviews, observations, and document analysis. The findings reveal that the implementation of Rumah Penting reflects an effective collaborative governance process. Initial conditions were characterized by limited resources but supported by social trust, prior collaboration, and shared commitment among stakeholders. Facilitative leadership played a significant role in creating an inclusive and participatory environment, enabling adolescents to act as agents of change in stunting prevention. Institutional support through local policies and the GenRe forum further strengthened youth participation, while the collaborative process was reflected in open communication, shared responsibilities, and collective ownership. These efforts generated tangible outcomes, including increased nutritional awareness, stronger family engagement, and improved adolescent capacity in stunting advocacy. Therefore, this study recommends strengthening institutional support, expanding adolescent-based collaborative initiatives, and replicating the Rumah Penting model to accelerate stunting reduction efforts in Indonesia.